Differential accumulation of cardenolides from Asclepias curassavica by large milkweed bugs does not correspond to availability in seeds or biological activity on the bug Na+/K+-ATPase - Rubiano-Buitrago, Paola; Pradhan, Shrikant; Grabe, Veit; Aceves-Aparicio, Alfonso; Paetz, Christian; Rowland, Hannah M. (Frontiers in Ecology and Evolution, 2023)
Milkweed–herbivore systems are characterised by cardenolide chemical defences and specialised herbivore adaptations such as physiological target site insensitivity. Cardenolide defences in milkweeds can vary in terms of the total concentration, differences in the polarity of individual cardenolides, and in the substitution of the steroidal structures that can contribute to the molecule’s reactivity. The variability in cardenolide defences could represent the plant’s response to natural selection and adaptation of resistant herbivores, and is a characteristic of phenotype-matching between defensive and offensive traits resulting from coevolution. Here we test the phenotypic match of the cardenolide composition of seeds of Asclepias curassavica and those sequestered by nymphs and adults of the specialised seed herbivore Oncopeltus fasciatus, combined with tests of the inhibitory capacity of a subset of seed cardenolides against the Na+/K+- ATPase of O. fasciatus and a non-adapted insect (Drosophila melanogaster). We compare this with the inhibitory capacity against the highly sensitive porcine Na+/K+-ATPase. Among the five most abundant cardenolides present in milkweed seeds, glucopyranosyl frugoside, glucopyranosyl gofruside, and glucopyranosyl calotropin were significantly more abundant in the seeds than in the adults and nymphs; the bugs contained higher concentrations of the deglucosylated compounds. The most abundant compound, glucopyranosyl frugoside, was also the most inhibitory for O. fasciatus, but O. fasciatus was significantly more tolerant to all compounds compared to D. melanogaster and the highly sensitive porcine enzyme. Our results add to the evidence that O. fasciatus sequesters specific individual cardenolides from its Asclepias host plants that is not a directly linked to the concentration and inhibitory potency.